Effect of temperature on the synthesis of centella asiatica flavonoids extract-mediated gold nanoparticles: uv-visible spectra analyses - Latif, Muhammad Sohail; Kormin, Faridah; Mustafa, Muhammad Kamarulzaki; Mohamad, Ida Idayu; Khan, Muhammad; Abbas, Sameera; Ghazali, Muhammad Ihsan; Shafie, Nor Shafawati; Abu Bakar, Mohd Fadzelly; Sabran, Siti Fatimah; Mohamad Fuzi, Siti Fatimah Zaharah (2018)
Many plants have been reported for the nanosynthesis of metal nanoparticles by virtue of the reducing potential of their bioactive compounds. Centella asiatica (CA) is one of the widely used plants, as claimed by traditional system of medicine, to have its positive effects on a variety of ailments. However, no research evidence indicates the synthesis of CA flavonoids extract (CACrF)-mediated gold nanoparticles (GNPs). In the present study, the initial synthesis of gold nanoparticles (GNPs) mediated by Centella asiatica crude flavonoids extract (CACrF) has been discussed. The protocol involves a one-step, non-toxic and cost effective procedure based on green nanotechnology avoiding the use of any synthetic chemicals potentially harmful for environment and biomedical applications. The CACrF was reacted with gold chloride, trihydrate (HAuCl4.3H2O) for the synthesis of GNPs. The reaction was carried out at room temperatures. The formation of GNPs was visually observed by a change in the color of solution from pale yellow to ruby pink. UV-visible (UV-vis) spectrophotomteric analysis was performed to verify the synthesis of CACrFmediated GNPs. As a function of time, the surface plasmon resonance (SPR) behavior of GNPs was evaluated to study the reaction kinetics and the UV-vis spectra were recorded after every 10 minutes up to 70 minutes. A single peak at 542 nm with absorbance of 0.475±0.039 indicated the synthesis of GNPs.